INTEGRASI EKONOMI DALAM ISLAM - Angga Syahputra (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2020)
Abstract Islam is order and harmony. The only teaching in the world that has a system and concept of a perfect arrangement of life. The completeness of these rules is in line with harmony with the characteristics and behavior of humans. Economics is an inseparable part of the concept of Islamic teachings. Islamic economics is inherently a logical consequence of the perfection of Islam itself. Islam must be embraced kaffah and by his people. Islam demands its followers to realize their Islam in all aspects of their lives including the economy. Keywords: Integration, Economic, Islam. Abstrak Islam adalah keteraturan dan harmoni. Satu-satunya ajaran di dunia yang memiliki sistem dan konsep tatanan kehidupan yang sempurna. Kesempurnaan ajaran tersebut sejalan dengan karakteristik dan perilaku manusia. Ekonomi merupakan bagian yang tidak terpisahkan dari konsep ajaran Islam. Ekonomi Islam pada dasarnya adalah konsekuensi logis dari kesempurnaan Islam itu sendiri. Islam harus dianut secara kaffah dan oleh umatnya. Islam mengajarkan ummatnya untuk mengaplikasikan Islam dalam semua aspek kehidupan mereka termasuk ekonomi. Kata kunci: Integrasi, Ekonomi, Islam.